Farmers Day Side Event: Partnering to Scale-Up Climate-Smart Agriculture in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Report back from Farmers Day Africa CSA Alliance side event at the UN Climate Change Conference. Photos: V. Atakos (CCAFS). Read more about this meeting: Innovative climate change partnerships bring hope for smallholder farmers in Africa.